Developmental encephalopathy and epilepsy associated with a heterozygous de novo mutation in the IRF2BPL gene: a case report - N. G. Lyukshina; A. A. Sharkov; E. N. Tolmacheva (Русский журнал детской неврологии, 2021)
Developmental encephalopathy with epilepsy or epileptic encephalopathy, associated with a heterozygous mutation in the IRF2BPL gene, is a rare severe disorder. It’s manifested by developmental delay or regression of skills until or after epilepsy onset. Patients have a specific facial phenotype, movement disorders with dystonia and choreoathetosis, ataxia, dysarthria, dysmetria, and dysdiadochokinesis. Epilepsy is a common manifestation of the disease (around 70 % of cases), from the age of 6 months to 26 years. Semiology of seizures is vary, including infantile spasms, myoclonic, tonic or clonic seizures with nonspecific electroencephalographic changes. magnetic resonance imaging shows normal brain development at an early age and cortical and cerebellar atrophy developing over time. The authors present a clinical case describing a patient with a causative de novo variant (c.2152delT) in the IRF2BPL gene in Russia.This patient was included to common table in an article entitled “De novo truncating variants in the intronless IRF2BPL are responsible for developmental epileptic encephalopathy” (DOI: 10.1038/s41436-018-0143-0).